Features of in vitro cultivation of the field strain of canine parvovirus - M. L. Radzyhovskyi; N. V. Kuryata; O. V. Pishchanskyi; O. V. Dyshkant; O. A. Androshchuk; I. M. Sokulskyi; V. V. Ukhovskyi; O. V. Rudoi (Біологія тварин)
Intestinal infections remain one of the most important health care problems. According to WHO, viral diarrhea is the most common infectious disease in the world. A similar situation is registered among the diseases of dogs, where enteritis of infectious etiology occupies a leading place, and the leader is parvovirus enteritis from which dog owners have been suffering for the past forty years. Despite such a long period of time, unfortunately, proper means of treatment and prevention have not been created, and taking into account the persistence of the virus in the external environment and the ability to mutate, the correlation of diagnostic methods is always necessary, which, accordingly, indicates the relevance of studying parvovirus infection in dogs. The use of cell cultures as test objects for the cultivation and accumulation of viral biomass makes it possible to obtain an antigen suitable for use in the manufacture of diagnostic, prophylactic and therapeutic biological preparations. The publication contains research materials on the peculiarities of the cultivation of canine parvovirus isolated on the territory of Ukraine from a 2-month-old purebred puppy that died of parvovirus enteritis. In the biological material isolated from the dead animal by means of laboratory studies, mono-infection and the possibility of its cultivation in vitro were established. The possibility of using a transplantable line of rabbit kidney cell culture (RK-13) has been established. Freshly reseeded, after 24 hours of incubation, with at least 70% and no more than 80% cell monolayer and seeding concentration from 1.0×105 to 2.0×105 cells/ml, as a biological test object for cultivation and accumulation parvovirus biomass. Cultivation was carried out in a thermostat at t = +37.5°C for no more than 10 days, and a mixture of medium 199 and DMEM was used as a supporting medium. The effectiveness of cultivation was determined by the increase in the titer of the infectious activity of the virus, which by the fifth passage was 3.8±0.08 lg TCD50/cm3.